Feasibility analysis of urban solar system and a proposition of renovated design in context of Bangladesh - karim, Saadman; Islam, S.M. Rahin; Sumon, Md. Shariful Islam; Kazim, Rida Al (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.